Are cardiovascular diseases bad for economic growth? - Marc Suhrcke; Dieter M. Urban (Center for Economic Studies and ifo Institute (CESifo), 2006)
We assess the impact of cardiovascular disease (CVD) mortality on economic growth, using a dynamic panel growth regression framework taking into account potential endogeneity problems. We start from a worldwide sample of countries for which data was available and detect a non-linearity in the influence of working age CVD mortality rates on growth across the per capita income scale. We then split the sample (according to the resulting income threshold) into low- and middle-income countries on one hand, and high-income countries on the other hand. In the latter sample we find a robust negative contribution of increasing CVD mortality rates on subsequent five-year growth rates. Not too surprisingly, we find no significant impact in the low- and middle-income country sample.
Keywords: I10; O47; 330